In-situ Sr isotope disequilibrium in plagioclases from Late Cenozoic basalts in Leiqiong area: Evidence for the role of the Hainan plume and mantle metasomatism due to a paleo-subduction event - Chen, Shuang-Shuang; Wu, Duo-Yang; Gao, Rui; Cheng, Qiuming; Liu, Jia-Qi (Frontiers in Earth Science, 2023)
The origin of the EM2 (enriched mantle 2)-type reservoir beneath the Southeast Asia is controversial. In this study, we present new in-situ major and trace element (olivine, clinopyroxene, and plagioclase), and Sr isotopic compositions (plagioclase) for Leiqiong basaltic rocks to explain the potential source of Leiqiong EM2-like reservoir. Leiqiong olivines show the normal zoning textures with in-situ trace element heterogeneity, Leiqiong plagioclases exhibit the complex zoning textures with in-situ 87Sr/86Sr isotopic disequilibria. It likely suggests the contribution to an individual crystal by the incorporation of heterogeneous components. The olivine and plagioclase phenocrysts, and the calculated Leiqiong clinopyroxene-equilibrium melts show the features of OIB-type enriched compositions associated with the plume, likely indicating the presence of Hainan mantle plume. The clear disequilibrium of 87Sr/86Sr isotopic ratios among bulk-rock, plagioclase phenocryst, and groundmass likely indicates the isotopically heterogeneous mantle source and the influence of the recycled subduction-related H2O-enriched oceanic fluid/melts carried by the deep Hainan plume. Leiqiong olivines are crystallized by the incorporation of pyroxenitic mantle source, but different from those from olivine-rich peridotitic mantle lithology, likely due to the reaction between eclogite-derived silicate melts (recycled oceanic crust) and peridotite.